Polyurethane Binder for Aqueous Processing of Li-Ion Battery Electrodes. Issue 14 (1st January 2015) - Loeffler, Nicholas; Kopel, Thomas; Kim, Guk-Tae; Passerini, Stefano
Abstract : In this manuscript the investigation of the heat-curable polyurethane (PU)/carboxymethyl cellulose (CMC) mixture as binder for Li-ion battery electrodes is reported. The experimental results demonstrate the outstanding thermal and electrochemical stability of PU, as well as the good electrochemical performance of cathode (NMC) and anode (graphite) electrodes in which PU is used as binder. The most important finding is the ability of PU to prevent current collector corrosion usually occurring when an aqueous dispersion (slurry) of NMC is coated on aluminum foils. SEM investigation shows that PU encapsulates the positive active material particles preventing a pH raise in the slurry. Finally, the cycling performance of PU/CMC based anodes and cathodes are tested in half as well as full lithium-ion cell setups.